A Quasi-Fideist Approach to QAnon. (4th May 2022) - Smith, Nicholas
ABSTRACT: QAnon, the view that Donald Trump is the last line of defense against a secret group of Satanic child traffickers, has garnered a great deal of traction and attention. A growing number of people describe themselves as having lost friends and relatives to QAnon, and many of us are unsure of how to interact with QAnon adherents. Intuitively, QAnon is a conspiracy theory. This might suggest that the right strategy is to debunk QAnon, because conspiracy theories are generally considered epistemically flawed views. However, this perspective may leave us ill-prepared to appreciate just how committed QAnon adherents are. To interact with them, we must find a way to take QAnon seriously, rather than dismissively. In this spirit, I argue for an alternative framework: we should treat QAnon as a religion. I first show that QAnon can reasonably be thought of as a religion. This opens the door to using tools from philosophy of religion to understand the epistemology of QAnon adherents. I use a quasi-fideist account of religious epistemology to explain why QAnon is a particularly recalcitrant worldview, and to develop an account of how one might 'convert' a QAnon adherent to a different worldview.